Effects of various freezing containers for vitrification freezing on mouse oogenesis. Issue 1 (December 2016) - Kim, Ji; Kim, Jae; Seo, Byoung
Abstract Background In the present study, various freezing containers were tested for mouse embryos of respective developmental stages; embryos were vitrified and then their survival rate and developmental rate were monitored. Mouse two cell, 8 cell, and blastula stage embryos underwent vitrification freezing-thawing and then their recovery rate, survival rate, development rate, and hatching rate were investigated. Methods EM-grid, OPS, and cryo-loop were utilized for vitrification freezing-thawing of mouse embryos. Results It was found that recovery rate and survival rate were higher in the group of cryo-loop compared to those of EM-grid (p < 0.05). Embryonic development rate, two cell embryos to blastocyst, as well as hatching rate were higher in the control group compared to the EM-grid group and OPS group (p < 0.05), yet no difference was noted between the control group and cryo-loop group. Development rate and hatching rate of eight cell morulae and blastocysts were all lower in the treatment groups than the control group whilst hatching rate of blastocysts was higher in the control group compared to the groups of EM-grid and OPS (p < 0.05); although the cryo-loop group was shown to be slightly higher than other groups, it was not statistically significant. Conclusions In the study, we investigate effects of freezing containers on vitrified embryos of respective developmental stages; it was demonstrated that higher developmental rate was shown in more progressed (or developed) embryos with more blastomeres. There was however, no difference in embryonic development rate was shown amongst containers. Taken together, further additional studies are warranted with regards to 1) manipulation techniques of embryos for various vitrification freezing containers and 2) preventive measures against contamination via liquid nitrogen.